Geraldinho Nogueira e a narrativa artesanal : tradição & modernidade na arte do narrador - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
In this paper titled "Geraldinho Nogueira and the Handcrafted Narrative: Tradition and Modernity in the Art of the Narrator" I tried to think about the representativeness of Geraldinho Nogueira (1918-1993) for the popular culture of Goiás,Brazil, through the insertion of the artisanal narrative within the scope of contemporaneity together. For these statements, Geraldinho’s causes proved to be important, because through them we had the opportunity to get into the universe of experience and coexistence of this Goiano causes teller. His universe is characterized mainly by the relationship of reciprocity among subjects, in sharing practices, cultural values and knowledge. Faced with the artistic notoriety that Geraldinho acquired with the people with whom he directly established relationships in the mid-1980s, he was taken to the media by Hamilton Carneiro, presenter of Frutos da Terra TV show. Quickly, the narrative causes teller became a phenomenon of criticism, becoming the weekly attraction of the respective program. The success that Geraldinho achieved in the television space, owes much to his ability to move through different social spaces. In addition to this ability to go through different realities, the Goiano narrative teller enchanted the viewers with plots full of humorous elements. However, besides the fun, this study aims to show that the laughter raised by Geraldinho also brings other indications, such as the transmission of a load of knowledge belonging to its cultural values, and also a positioning of the subject / teller / narrator before the "braveness" of the world. Thus, I intend to make a relation of the causes made and communicated by Geraldinho, relating them to the concept of artisanal narrative defended by Benjamin (2012), trying to perceive the factors that made the artisanal narrative to fit in and adapt to the contemporary world.
Keywords: Causos; Narrativa Popular; Narrativa Popular - Geraldinho; Narrativa popular - Goiana - Geraldinho; Causos - Geraldinho; Causes; Narrative Popular; Narrative Popular - Geraldinho; Narrative Popular - Goiana - Geraldinho; Causes - Geraldinho; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::SOCIOLOGIA; LETRAS::LITERATURA BRASILEIRA